Factors Associated With Blood Pressure Control Among Patients In A Primary Health Care Center: A Cross-Sectional Study - Servia Mokar; Dian Pitaloka Priasmoro (Akademi Keperawatan Yarsi Samarinda, 2026)
Background: Hypertension remains a major public health problem and is influenced by demographic, clinical, and behavioral factors. Understanding these factors is essential for effective blood pressure control, particularly in primary health care settings. Objective: This study aimed to analyze the association between demographic, clinical, and behavioral characteristics and blood pressure status among patients at a primary health care center. Methods: A cross-sectional study was conducted using secondary data obtained from medical records at Wayabula Primary Health Care Center, Pulau Morotai Regency, Indonesia, collected between October and December 2025. A total of 69 patient records were included. Data were analyzed using SPSS version 26. Descriptive statistics were presented as frequencies and percentages. Associations between variables and blood pressure status were examined using chi-square or Fisher’s exact tests, with a significance level of p < 0.05. Results: Most participants were adults, male, and employed, with normal nutritional status and controlled blood pressure. Significant associations were found between blood pressure status and age group, gender, employment status, and smoking status (p < 0.05). Educational level, nutritional status, and physical activity were not significantly associated with blood pressure status. Conclusion: Demographic and behavioral factors, particularly age, gender, employment status, and smoking, were significantly associated with blood pressure status. These findings highlight the importance of targeted interventions in primary health care to improve hypertension control.